Reversible Intraoperative Neurophysiologic Monitoring Alerts in Patients Undergoing Arthrodesis for Adolescent Idiopathic Scoliosis: What Are the Outcomes of Surgery? - Samdani, Amer F; Bennett, James T; Ames, Robert J; Asghar, Jahangir K; Orlando, Giuseppe; Pahys, Joshua M; Yaszay, Burt; Miyanji, Firoz; Lonner, Baron S; Lehman, Jr, Ronald A; Newton, Peter O; Cahill, Patrick J; et al. (Journal of bone and joint surgery. American volume, 2016)
Confidence in intraoperative neurophysiologic monitoring (IONM) data can allow scoliosis surgeons to proceed with surgery even after a monitoring alert, assuming the recovery of signals. We sought to determine the outcomes of surgical treatment of adolescent idiopathic scoliosis (AIS) after a notable IONM alert. We identified 676 patients who underwent arthrodesis with use of IONM for the treatment of AIS. The patients were divided into 2 cohorts: those who experienced a lower-extremity IONM alert and those who did not. An alert was defined as a notable change in IONM data, specifically, a ≥50% drop in somatosensory evoked potentials (SSEPs) and/or in transcranial motor evoked potentials (tcMEPs). Of the 676 patients, 36 (5.3%) experienced IONM alerts. Those patients had a larger preoperative major Cobb angle (mean of 61° ± 13° compared with 55° ± 12° for the no-alert group; p < 0.01), a greater number of levels fused (mean of 12 ± 2 compared with 11 ± 2; p < 0.01), a longer operative duration (mean of 357 ± 157 minutes compared with 298 ± 117 minutes; p < 0.01), a higher estimated blood loss (1,857 ± 1,323 mL compared with 999 ± 796 mL; p < 0.01), and a greater volume of autologous blood transfused (mean of 527 ± 525 mL compared with 268 ± 327 mL; p < 0.01). Among patients who experienced an alert and had a completed operation (34 of 36 patients), mean postoperative radiographic measurements were similar to those of the no-alert group in terms of the percentage of correction of the major Cobb angle (alert, 66% ± 13%; no alert, 64% ± 19%; p = 0.53) and of rib prominence (alert, 49% ± 36%; no alert, 47% ± 46%; p = 0.83) and measurement of thoracic kyphosis (alert, 23° ± 10°; no alert, 22° ± 2°; p = 0.58). The Scoliosis Research Society (SRS)-22 outcome scores were also similar between the 2 cohorts. Notable IONM changes occurred in 5.3% of the patients who underwent arthrodesis for AIS. Those patients had larger preoperative deformity, a longer operative duration, a greater number of levels fused, a higher estimated blood loss, and a greater volume of autologous blood transfused. Return of IONM data guided the surgeon to safely complete the procedure in 34 of 36 patients, with correction similar to that of patients who did not experience an alert. Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.